REDISCOVERY OF RHAGIO CHRYSOSTIGMA (LOEW, 1857) (DIPTERA: RHAGIONIDAE) (Acta Entomologica Serbica, 2021)
The rediscovery of Rhagio chrysostigma (Loew, 1857) after ca. 90 years, as well as the first record from Slovenia, are presented. The published data of this species are known only from northeastern Italy and are based on old records (Loew 1857, Schiner 1862, Szilády 1934).